Non … delinquere eum, qui in dubiis quaestionibus contra fiscum … responderit. About freedom of speech of lawyers - Sitek, Bronisław (Journal of Modern Science, 2018)
The subject of this study is the analysis of the text of Modestinus D. 49.14.10. This is an excerpt rarely interpreted by Romanists. The aim of this analysis is to show its significance for the author, Justinian compilers and contemporary romanists. The implementation of this goal is achieved through the application of the legal-historical and dogmatic analysis of this text. The most important, however, is the analysis of the original location by Modestyn. This will allow showing the meaning that the author gave him. The result of these interpretive procedures is the demonstration that it was a text guaranteeing the freedom of oral and written expression of advocates or trial lawyers in the judicial proceeding against the tax office. Thus, the fragment of Modestinus became an archetype of modern lawyer’s immunity, consisting in the possibility of free discussion and argumentation during court hearings and in legal opinions.